2020
DOI: 10.1111/pace.13867
|View full text |Cite
|
Sign up to set email alerts
|

Optimal diameter of the pulmonary vein ostium for second‐generation 28‐mm cryoballoon ablation of atrial fibrillation

Abstract: Background Large pulmonary veins (PVs) have the risk of excessive cooling when the cryoballoon is moved into them, whereas smaller PVs may not be isolated because of insufficient balloon‐tissue contact. We previously reported that the effective nadir balloon temperature (NBT) was <− 44°C for predicting early PV reconnections. However, the ideal PV and left atrial (LA) diameters for cooling temperatures during cryoballoon ablation (CBA) are unknown. Methods We measured the PV ostium (PVos) and LA diameters on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This characteristic was thought to be an advantage to improve PV occlusion and avoid the pop-out phenomenon, improving balloon-to-tissue contact. 8 , 18 Despite that, our study confirmed that in experienced hands, the total number of freeze applications, and the applications for each PV did not differ between the two technologies.…”
Section: Discussionsupporting
confidence: 67%
“…This characteristic was thought to be an advantage to improve PV occlusion and avoid the pop-out phenomenon, improving balloon-to-tissue contact. 8 , 18 Despite that, our study confirmed that in experienced hands, the total number of freeze applications, and the applications for each PV did not differ between the two technologies.…”
Section: Discussionsupporting
confidence: 67%
“…26 While our study focused on mid-term outcomes following CBA, other studies have evaluated parameters of acute procedural success such as degree of occlusion and nadir balloon temperature in relation to PV diameters, ostial area and ovality indices. 12,16,27 Our study is a first of its kind evaluating whether the presence of an atypical PV anatomy or PV anatomic characteristics predict mid-term outcomes exclusively in paroxysmal AF patients. Although constrained by a small sample size, our results did not show any particular association between PV anatomy and CBA failure in paroxysmal AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…(1) EI=PVmaxD/PVminD, 16 (2) OI = 2 x (PVmaxD-PVminD/PVmaxD+PVminD) 16 and 3PVA= π x PVmaxD x PVminD. PV EI values between 1.2-1.4 were representative of ovality while <1.2 were circular and > 1.4 considered as flat.…”
Section: Pulmonary Vein Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preprocedural anatomy of LA and PVs acquired with 64-row-multidetector computed tomography (CT) (Somatom Definition AS+, Siemens, Berlin, Germany) was available in 53% (156/296) of patients ( Figure 1 ). The following indices were obtained from multiplanar reconstructed images for each of the PVs using dedicated calliper software [ 19 ]: PV maximum (PVmax) and minimum (PVmin) ostial diameter, PV elliptical area calculated as (PVmax/2) × (PVmin/2) × 3.14 and the ovality index calculated as PVmax/PVmin.…”
Section: Methodsmentioning
confidence: 99%